Human muscle sympathetic nerve responses to urocortin‐2 in health and stable heart failure. (25th August 2015) - Chan, W Y Wandy; Charles, Christopher J; Frampton, Christopher M; Richards, A Mark; Crozier, Ian G; Troughton, Richard W; Jardine, David L
Summary Sympatholytic and vasodilator drugs have been of major therapeutic benefit in patients with heart failure (HF). Urocortin‐2 (Ucn2) is a small corticotrophin‐related peptide distributed throughout the cardiovascular system which inhibits cardiac sympathetic nerve activity (CSNA) and is also a powerful vasodilator. This study analysed the effects of a 60‐min infusion of Ucn2 (25 μg) on muscle sympathetic nerve activity (MSNA) recorded from the lower limb in eight healthy men and four men with stable HF. During Ucn2 infusion, mean arterial pressure fell to a nadir of 84 ± 2 compared to 95 ± 2 mmHg during placebo (P = 0.001) and heart rate increased to a maximum of 74 ± 1 compared to 64 ± 1 b.p.m. (P < 0.001). Total peripheral resistance fell by 23 ± 4% compared with an increase of 23 ± 4% (P < 0.001) and cardiac output increased by 22 ± 4 compared to 4 ± 4% (P = 0.001). The MSNA burst frequency increased by 9 ± 2 compared to 1 ± 2 burst/min (P = 0.005) and burst area/min by 133 ± 7 vs 107 ± 7% (P = 0.01). Burst incidence and baroreflex sensitivity were not significantly altered. Qualitatively similar changes were observed in stable HF patients. Ucn2‐induced vasodilatation increased MSNA in humans, as opposed to the decrease in CSNA we observed in sheep. Therefore, if Ucn2 has a central inhibitory effect on MSNA, it was over‐run by off‐loading the cardiovagal baroreflex. Alternatively, CSNA may be less responsive to baroreflex off‐loading than MSNA.